Possibilities for teacher’s preventive actions in regard bullying behavior of students - Marković Marija R. (Temida)
Prevention of school bullying is an important task of modern educational process, given the seriousness of its consequences for students who behave violently and for those who are exposed to bullying, as well as for other classmates. A teacher, who in comparison with other school staff is in daily contact with students, has an extremely important role in prevention of bullying and in creating encouraging school climate. Through systematized and critical reflection on the views of numerous authors, this article aims at pointing out importance of certain aspects of teachers‘ role in prevention of bullying, and importance of creating a positive school climate as an important prerequisite for preventive activity of teachers, as well as at emphasizing possible obstacles to adequate preventive actions of teachers. In the last section, changes made in recent years in Serbia in regard to prevention of bullying behavior of students in the education system are considered. [Projekat Ministarstva nauke Republike Srbije, br. 179013: Održivost identiteta Srba i nacionalnih manjina u pograničnim opštinama istočne i jugoistočne Srbije]